Coronavirus and Face-to-Face Learning in Higher Education: Students’ Nosophobia of Covid-19 - Korkmaz, Celalettin (My University, 2022)
This study aims to evaluate the effectiveness of face-to-face education in the pandemic with a mixed methodology according to the Covid-19 phobias and anxiety levels of higher education students. The research was designed within the framework of convergent simultaneous mixed research design. Quantitative data were obtained by using a Covid-19 phobia questionnaire with the participation of 248 higher education students in a university located in the Mediterranean region of Turkey. Qualitative data were collected by using an open-ended question about the anxiety of catching the disease with the participation of 64 students. The first part of the scale includes demographic informations. In the other parts, there are 20 question items in 5-point Likert type, and an open-ended question statement was included in order to enable different opinions to be expressed. Normally distributed quantitative data were analyzed using statistical programs, and qualitative data were analyzed using content analysis method to describe participant views. The results of the research reveal that university students have Covid-19 phobia in the face-to-face education process, and the phobias differ significantly according to the type of vaccine and the presence of people they are worried about infecting. On the other hand, it was determined that the place of residence doesn’t have a significant effect on the Covid-19 phobia of the students. In addition, students explain their anxiety about getting sick in the context of environmental, individual, and educational factors. Ethics committee approval for this study was obtained with the decision of Hatay Mustafa Kemal University Social and Human Sciences Scientific Research and Publication Ethics Committee, dated 05.01.2022, meeting 01 and number 08.